A comparison of the brief international cognitive assessment for multiple sclerosis and the brief repeatable battery in multiple sclerosis patients. Issue 1 (December 2015) - Niccolai, Claudia; Portaccio, Emilio; Goretti, Benedetta; Hakiki, Bahia; Giannini, Marta; Pastò, Luisa; Righini, Isabella; Falautano, Monica; Minacapelli, Eleonora; Martinelli, Vittorio; Incerti, Chiara; Nocentini, Ugo; et al.
Abstract Background Recently, a Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) has been developed as an international and standardized brief cognitive test, which is easily performed in everyday clinical practice for neuropsychological assessment in multiple sclerosis (MS). However, we need to gather more information about this tool compared to other neuropsychological batteries. The aim of our study is to compare the performance of BICAMS and Brief Repeatable Battery (BRB) in MS subjects. Methods Tests of the BRB and BICAMS were administered to MS patients recruited from 11 Italian MS centres. Cognitive impairment (CI) was defined as the failure on at least two tests (scores below the fifth percentile) on the BRB and as the failure on at least one test of the BICAMS. The agreement between the performances on the two batteries was assessed through Cohen's K statistic. Finally we calculated the effects sizes for each test of the two batteries using Cohen's d. Results The two batteries were administered to 192 MS patients (142 women, 50 men; mean age 41.4 ± 10.8 years, mean education 12.3 ± 3.5 years). Mean scores of patients were lower compared to those of healthy subjects in all the cognitive measures examined. Forty-six MS patients were identified as impaired and 48 as unimpaired on both of the batteries, when the Symbol Digit Modalities Test (SDMT) was included in the analysis. Cohen's K statistic was 0.46 which corresponds to a moderate accord. If the SDMT was excluded from the BRB, 37 MS patients were identified as impaired and 57 as unimpaired on both of the batteries. Cohen's K statistic was 0.3 which corresponds to a poor accord. The SDMT, the Paced Auditory Serial Addition Test (PASAT) 3 and 2 yielded higher d values (SDMT 0.83, PASAT 3 0.65, PASAT 2 0.84). Conclusions This study confirms the feasibility of BICAMS in everyday clinical practice for the identification of CI and highlights the good psychometric properties of the SDMT.